A Serra do Periperi e as implicações socioambientais decorrentes da expansão urbana de Vitória da Conquista - BA - Silva, Iguaraci Santos da (2013)
Issues relating to the environment are discussed in the various summits of human development, education and health, to understand the natural and anthropogenic environmental metamorphosis that occurs on the Earth. In this context, the purpose of this study was analyzing the Serra do Periperi and the environmental implications caused in this geomorphological unit, resulting from urban expansion at Vitória da Conquista. In order to accomplish the aim of the preceding paragraph, and other specific objectives, we used different methodological procedures associated with two steps: the office and field. In office, we did the bibliographical survey and cartographic documents, beyond the preparation of specific thematic maps of the physical environment to support discussion of geo-environmental conditions. In the field research, in addition to direct observations of the impacts on the landscape prints, it was also conducting interviews. The results of this study show that, in the specific case of occupations in the Serra do Periperi, the elements that make up the geo-environmental conditions are being affected by the process of sprawl toward the mountains, such as: climate aspects, geological, geomorphological, pedological and vegetation with specific features, which interrelated maintain the dynamic balance of this geomorphological unit so important to Vitória da Conquista county. However, this balance has been affected by anthropism which in turn interfered these constraints transforming them into fragile elements, and consequently may trigger various environmental problems that affect the conquistense population as a whole. Therefore, we conclude that the issues related to environmental impacts involving Serra do Periperi originated in the colonial period and have been perpetuated to the present day, causing inconvenience to the city in general, without the municipal public administration adopt more effective measures to combat degradational processes of the landscape.